2004
DOI: 10.1534/genetics.167.1.485
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Locus Mapping Based on Resampling in a Vast Maize Testcross Experiment and Its Relevance to Quantitative Genetics for Complex Traits

Abstract: From simulation studies it is known that the allocation of experimental resources has a crucial effect on power of QTL detection as well as on accuracy and precision of QTL estimates. In this study, we used a very large experimental data set composed of 976 F 5 maize testcross progenies evaluated in 19 environments and cross-validation to assess the effect of sample size (N ), number of test environments (E ), and significance threshold on the number of detected QTL, the proportion of the genotypic variance ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
170
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(186 citation statements)
references
References 25 publications
12
170
3
1
Order By: Relevance
“…The poor precision of QTL effect estimation is also reflected in the large range of estimated p G ÀES and p G ÀTS values (Figure 4). Our results corroborate previous findings (Schön et al, 2004;Liu et al, 2013) as we observed an average relative bias of 38%. This is higher than what was observed in a previous study using the same data set where a cross-validation was used assuming the QTL detected with the full data set as fixed (Würschum et al, 2011a).…”
Section: Predictive Power and Its Biassupporting
confidence: 93%
See 2 more Smart Citations
“…The poor precision of QTL effect estimation is also reflected in the large range of estimated p G ÀES and p G ÀTS values (Figure 4). Our results corroborate previous findings (Schön et al, 2004;Liu et al, 2013) as we observed an average relative bias of 38%. This is higher than what was observed in a previous study using the same data set where a cross-validation was used assuming the QTL detected with the full data set as fixed (Würschum et al, 2011a).…”
Section: Predictive Power and Its Biassupporting
confidence: 93%
“…Recent work has shown this parameter to be overestimated with a relative bias between 10 and 60% depending on the population and the complexity of the trait (Utz et al, 2000;Schön et al, 2004;Liu et al, 2013). This reduction of p G ÀTS as compared with p G ÀES indicates a large upward bias in predictors of the proportion of explained genotypic variance, that is, QTL effects inferred from the ES.…”
Section: Predictive Power and Its Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Different conclusions regarding the number, magnitude, and distribution of QTL for complex traits might be drawn if larger populations were evaluated (29,30). Comparing LD mapping of 305 lines versus 522 lines demonstrates the beneficial effect of larger population size in this study (Table S6).…”
Section: Discussionmentioning
confidence: 79%
“…Genetic variation for complex traits, such as yield potential in elite maize populations, is controlled by many genetic factors, each with relatively small effects (Schö n et al, 2004;Holland, 2007). Therefore, the usage of QTL mapping and marker-assisted selection approaches for yield potential in maize is questionable (Holland, 2004).…”
Section: Introductionmentioning
confidence: 99%